Predation on two dendropsophus species (Anura: Hylidae) by a Pisaurid spider in the Atlantic forest, Southeastern Brazil - Parelli Bovo, Rafael [UNESP]; de Oliveira, Eliziane Garcia [UNESP]; Nicioli Bandeira, Lucas [UNESP] (My University, 2014)
We report on two successful events of predation (and one attempt) on the hylid frogs Dendropsophus microps and D. minutus (Anura: Hylidae) by the spider Thaumasia velox (Araneae: Pisauridae) in the Brazilian Atlantic rainforest. Although never previously reported, our observations indicate that this spider species may constitute an important predator for small frogs of Brazilian Atlantic rainforest anuran communities.
Keywords: Amphibia; Neotropical region; Water spider